Aktual'nye problemy vidy sporta - Rodichenko, V. S. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The actual problems of a kind of sport, including the available contradictions inside of it and in its external connections, its present difficulties and unsolved tasks, are investigated insufficiently. Some results of the long-term research of these problems, their identification and the grouping to the chosen attributes are stated in the article. The general number of the selected problems most widespread in various kinds of sport has made 95. All problem fields were divided into 7 problem zones, 2-3 problem areas were isolated in everyone. Inside of each area, the problems at the given investigation phase are located without taking into account their importance and the level of the organizations which are the subjects to these problems. The development of the nomenclature of problems will draw the attention to the activization of the decision of each of them, and then to carry the proved and approved solves to other kinds of sport. The nomenclature of problems also can be used in the educational process.